Assessing the Ethical Behavior of Accounting Accounts Through the Application of the Tri Kaya Parisudha Philosophy on Equity Sensitivity and Ethical Sensitivity - Mertyani Sari Dewi; Komang Trisna Sari Dewi; Made Dwi Ferayani (Universitas Pendidikan Ganesha, 2021)
The government must pay attention to the ability of its employees because it has accountability that can develop a sound and well-established reporting system. The government must pay attention to the ability of its employees because it has accountability that can develop a sound and well-established reporting system. The purpose of this study was to examine the sensitivity and ethics to the behavior of accounting actors and to examine the philosophy of Tri Kaya Parisudha, which is one of the local variables of the Balinese Hindu genus which can strengthen the effect of sensitivity and sensitivity on ethical behavior. The method used in this research is the Component-based SEM, Partial Least Square (PLS) analysis method. A questionnaire technique was used as a data collection tool to obtain data. Questionnaires will be distributed to 25 OPD Bangli Regency. The test results show empirical evidence that equity sensitivity has a significant positive effect on the behavior of accounting actors. Second, ethical sensitivity has a significant positive effect on the ethical behavior of accounting actors. Third, the philosophy of Tri Kaya Parisudha strengthens the influence of ethical sensitivity on the behavior of ethical accounting actors. Fourth, Tri Kaya Parisudha's philosophy strengthens the influence of ethical sensitivity on the behavior of ethical accounting actors.